WORK CULTURE AND COMPETENCE: THEIR IMPACT ON THE PERFORMANCE OF NATIONAL MILITARY PERSONNEL - Ahmad, Ibrahim (Universitas Islam Lamongan, 2024)
This research aims to examine and comprehend the impact of work culture and competence on the performance of personnel in Bakangdam XIV Hasanuddin. The research method employed is a quantitative approach. The population under study comprises all personnel of Bekangdam XIV Hasanuddin, totaling 296 individuals. Sampling was conducted using the Slovin method, resulting in 196 respondents. Data collection was facilitated through the utilization of a Likert scale with a measurement range from 1 to 5. Questionnaires were distributed online using Google Forms. Data analysis encompassed tests for response characteristics, validity, reliability, and multiple linear regression. The findings reveal that work culture has a positive yet nonsignificant influence on personnel performance, whereas competence demonstrates a positive and significant impact. Partial analysis indicates that the competence variable dominates with a 90.5% influence on personnel performance. Simultaneously, both work culture and competence significantly and positively affect personnel performance by 58%, while the remaining 42% is attributed to unidentified factors. Consequently, enhancing work culture and competence among personnel is paramount for improving their performance in Bakangdam XIV Hasanuddin. It is hoped that all personnel will continually enhance their competence through training, qualification upgrades, and further education to enhance their knowledge, skills, and attitudes.